2003
DOI: 10.1038/sj.pcan.4500625
|View full text |Cite
|
Sign up to set email alerts
|

Randomised crossover trial to assess the tolerability of LHRH analogue administration

Abstract: Luteinising hormone releasing hormone (LHRH) analogues are routinely used in the treatment of patients with advanced prostate cancer. This randomised crossover trial was conducted to compare patient comfort and tolerability between two commonly used LHRH analogues: goserelin acetate and leuprorelin acetate. A total of 50 patients were randomised into two groups, each receiving 6-monthly injections of leuprorelin acetate (a liquid presentation) and goserelin acetate (a depot pellet) and crossing over between tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Williams et al demonstrated that the tolerability of leuprorelin acetate was better than that of goserelin acetate by a randomized crossover trial. The use of a 16-gauge needle for goserelin acetate rather than a 23-gauge needle of leuprorelin acetate may influence their results [1]. On the other hand, Montgomery et al [2] demonstrated that there was no significant difference in pain intensity between goserelin acetate and leuprorelin acetate when patients received them in a blinded manner.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Williams et al demonstrated that the tolerability of leuprorelin acetate was better than that of goserelin acetate by a randomized crossover trial. The use of a 16-gauge needle for goserelin acetate rather than a 23-gauge needle of leuprorelin acetate may influence their results [1]. On the other hand, Montgomery et al [2] demonstrated that there was no significant difference in pain intensity between goserelin acetate and leuprorelin acetate when patients received them in a blinded manner.…”
Section: Discussionmentioning
confidence: 97%
“…Conflicting results have been reported regarding pain associated with goserelin acetate injection. A randomized crossover study demonstrated that patients preferred injection of leuprorelin acetate via a smaller needle than goserelin acetate using a larger needle [1]. However, in contrast, another study showed that if injection was performed with the patient blinded, injection pain intensity was not significantly different between leuprorelin acetate administration with a small needle and goserelin acetate administration using a larger needle [2].…”
Section: Introductionmentioning
confidence: 92%
“…Injection pain is tolerable for most patients, though some complain of pain with the injection of goserelin acetate. A randomized, non-blinded, crossover study demonstrated that patients experienced less pain with the smaller needle used to administer leuprorelin acetate than with the larger needle used to administer goserelin acetate [3]. In contrast, Montgomery et al [4] reported that if injection was performed with the patient blinded, injection pain intensity did not differ significantly between leuprorelin acetate and goserelin.…”
Section: Introductionmentioning
confidence: 99%
“…16 It has previously been suggested that patients tolerate the administration method of leuprorelin acetate better than that of goserelin acetate. 15 Williams et al 15 performed a 2-arm crossover study of the two drug formulations, which involved 50 patients and demonstrated a statistically significant difference between the groups in favour of leuprorelin acetate. However, the differences may not have been clinically relevant; mean VAS discomfort scores for both treatments were at the lower end of the scale and all values were classed as mild immediately after injection.…”
Section: Commentmentioning
confidence: 99%
“…14 Previously, a randomised, nonblinded, crossover trial suggested that patients with prostate cancer experienced less pain with and preferred the smaller needle used to administer leuprorelin acetate compared with the larger needle used to administer goserelin acetate. 15 However, our clinical impression has been that patients experience little difference in the pain from injection of the two drugs when they are unaware of needle size. Therefore, a single-blind study was carried out to investigate if there is any difference in the pain experienced by patients from injection of the LH-RH analogues goserelin acetate and leuprorelin acetate when they are unaware of the needle size used to administer study treatment.…”
Section: Introductionmentioning
confidence: 99%